The Research of Feasibility and Efficacy of Radiofrequency Ablation in Treating Uterine Fibroids. Issue 47 (November 2015) - Luo, Xin; Shu, Shan-rong; Ma, Xue-feng; Shuai, Han-lin
Abstract : Abstract: To explore the feasibility and efficacy of radiofrequency ablation in treating uterine fibroids. Ninety patients with multiple uterine fibroids, who had undergone hysterectomy were included in the study. After the uterus was resected, the temperature of 60, 80, 100°C were adopted to ablate the in vitro fibroid with each temperature dealing with 30 patients. Simultaneously, 5 patients were included, whose in vivo fibroid were ablated with the temperature of 100°C before the fibroids were removed after laparotomy. After the fibroids were ablated, the smooth muscle in the ablated center (group A), the ablated edge (group B) and 1 cm away from the ablated edge (group C) were taken. Then, the samples were stained with hematoxylin and eosin (HE) to examine the histopathological changes, and immunohistochemistry was performed to detect the expression of estrogen receptor (ER) and progesterone receptor (PR). After radiofrequency ablation, the ablated lesions were round, toast tan, and dry on gross appearance. There were no obvious tissue carbonization and there were distinct boundary from periphery tissue. In vitro: On automated analysis, the average optical density of ER and PR in group A, B, and C was lower than the control group ( P  < 0.05), and which were gradually raised with the increased distance to electrode. In the same treatment group, ER optical density was gradually decreased with the increased temperature among 3 different groups. The PR optical density was decreased with the increased temperature under different temperatures in group A and group B, there was significant difference among groups ( P  < 0.05). But in group C, there was no difference in PR expression among the temperature of 60, 80, and 100°C ( P  > 0.05). In vivo: Compared with the control group, the average optical density of ER and PR were significantly different among group A, B, and C ( P  < 0.05), what's more, it was gradually raised with the increased distance to electrode. After radiofrequency ablation, the tissues displayed coagulative necrosis, and decreased ER and PR expression. Radiofrequency ablation may be considered a minimally invasive alternative for those women who wish to retain their reproductive potential. Eighty degree Celsius was expected to be the optimum temperature in radiofrequency ablation treatment of uterine fibroid.